Strategic Export Subsidies and Reciprocal Trade Agreements: The Natural Monopoly Case - Kyle Bagwell; Robert W. Staiger (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1996)
Why do governments seek restrictions on the use of export subsidies through reciprocal trade agreements such as GATT? With existing arguments, it is possible to understand GATT's restrictions on export subsidies as representing an inefficient victory of the interests of exporting governments over the interests of importing governments. However, to our knowledge, there does not exist a formal theoretical treatment that provides circumstances under which GATT's restrictions on export subsidies can be given a world-wide efficiency rationale. In this paper, we offer one such treatment in the context of a natural monopoly market. We emphasize that subsidy competition between governments can serve to coordinate the entry decisions of firms, finding that consumers in the importing countries may suffer if the coordination afforded exporters by government subsidy programs does more to prevent entry than to promote it. In such circumstances, we show that the existence of export subsidy programs can lead to inefficiencies, and importing countries and the world as a whole can be better off when such programs are banned.
Keywords: 330